Psychosocial Perspective in Analysis of Potential Work Hazards in Company X - Muhammad Ghazali Bagus Ani Putra (Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to analyze the potential for occupational hazards caused by psychosocial problems in company X. For representation of product service operations, 5 research locations were selected, namely aviation, lubricants, asphalt, fuel and LPG. A qualitative research method with an open snow ball sampling technique was carried out in order to get 30 participants for interviews and focus group discussions. Then the data were analyzed using thematic analysis which resulted in themes of psychosocial problems that occurred which could pose potential work hazards. To determine the core problem and causal flow of psychosocial aspects, stream analysis is used. This analysis shows that management who does not care about work facilities causes work equipment not to support work safety standards. Besides that, the quality of human resources who are less aware of work safety and stressful conditions due to workload causes non-compliance with SOPs so that it becomes a potential occupational hazard. It is this core problem that comes from a psychosocial perspective that must be addressed to minimize work hazards.